PERSEPSI MASYARAKAT UNTUK KEBERADAAN EKOSISTEM LAMUN DI TELUK YOUTEFA, JAYAPURA (PENDEKATAN WILLINGNESS TO PAY) - Baigo Hamuna; Basa T. Rumahorbo; Henderina J. Keiluhu; Alianto Alianto (Universitas Lambung Mangkurat, 2018)
Seagrass ecosystem in Youtefa Bay is very important and useful for the local people’s lives in around the Youtefa Bay. Willingness to Pay (WTP) of the locals toward the seagrass ecosystem is their appreciation for the existing value of seagrass ecosystem. This research explored how much the WTP was given by the local people toward the existences of seagrass ecosystem in Youtefa Bay. The data collection was conducted in March to April 2018 located in three villages around the Youtefa Bay, namely Tobati, Enggros and Nafri Villages as many as 228 respondents. Data analysis of this research was quantitative analysis to find out the mean WTP, aggregate and attribute WTP that influenced WTP value. The result of this research showed that there were 202 respondents were willing to contribute or pay and 26 respondents were not. The obtained WTP value of respondents ranged between IDR 0 to IDR 200,000.00 with mean WTP of respondent was Rp 53,464.91/year meanwhile aggregate WTP was Rp 27,480,964.91/year. Variables which had significant influence toward WTP value were participation at seminaries/trainings regarding coastal ecosystem. Meanwhile gender, age, education level, income, and profession or job variables didn’t make any significant influence toward the given WTP value amount.